Analysis of production costs and value of flue gas and carbon dioxide capture processes from enterprises and facilities of the energy complex as main sources of CO2 for implementation of water-gas methods of EOR - Klimov Dmitry; Drozdov Alexander (E3S Web of Conferences)
The article analyses the production costs of flue and carbon dioxide gas capture from enterprises and facilities of the energy complex as the main source of raw materials for the application of gas methods of enhanced oil recovery. The article discusses the advantages of using carbon dioxide as part of the global story of reducing the carbon footprint of industrial enterprises. The article also addresses the issues of evaluating the economic viability of CO2 capture technologies, considering cost, energy consumption and various factors affecting process costs. In addition, an economic indicator of technological efficiency such as the estimation of CO2 avoidance costs in various industries in need of decarbonisation measures is discussed. The importance of standardisation and methodology for estimating decarbonisation costs is highlighted, as well as the need to account for uncertainties in techno-economic indicators for an in-depth analysis of different technologies and their impact on production processes.